What Drives Enforced Compliance? Insights from the Extended Slippery Slope Model among Value Added Taxpayers - Rosalita Rachma Agusti; Brillyanes Sanawiri; Ari Irawan (Universitas Mercu Buana, 2026)
Objectives: This study examines the interrelationships among coercive power, implicit trust, antagonistic climate, and enforced tax compliance within the theoretical framework of the Extended Slippery Slope Framework.Methodology: Utilizing a quantitative research design, data were collected from 359 Value Added Taxpayers in East Java, Indonesia. The analysis focuses on how taxpayer perceptions of institutional authority influence their compliance behavior.Finding: Empirical results reveal that coercive power significantly exacerbates the emergence of an antagonistic climate, whereas implicit trust exerts a mitigating effect. Furthermore, an antagonistic climate is positively associated with enforced compliance, indicating that taxpayer adherence in such contexts is driven more by perceived institutional pressure than by intrinsic moral obligation. Mediation analysis further substantiates the role of antagonistic climate as a significant intermediary in the relationships between coercive power and enforced compliance, as well as between implicit trust and enforced compliance.Conclusion: These findings contribute to the growing body of behavioral tax literature by highlighting the psychological mechanisms that underpin compliance behavior. The results advocate for a dual-strategy approach in tax administration that integrates both enforcement mechanisms and trust-enhancing interventions to foster sustainable tax compliance over the long term.